2001
DOI: 10.3354/meps223121
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphosis of broadcast spawning corals in response to bacteria isolated from crustose algae

Abstract: External chemical signals provide a mechanism for broadcast-spawning scleractinian corals to recognise suitable substrata for larval settlement and metamorphosis. These morphogens can be extracted from crustose coralline algae (CCA) and the skeletons of some coral species, however the precise origin of the chemical inducers has not yet been conclusively demonstrated. Microorganisms have been reported to induce metamorphosis in various species of echinoderms, molluscs, polychaetes and cnidarians. We report that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
197
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(221 citation statements)
references
References 39 publications
12
197
2
3
Order By: Relevance
“…Furthermore, this and other studies have demonstrated some connection between metamorphosis of marine invertebrate larvae and bacterial species of the genus Pseudoalteromonas (Hadfield 2011). Species belonging to this genus have been shown to induce settlement of the larvae of the hydrozoan Hydractinia echinata (Müller 1973, Seipp et al 2007) and the corals Acropora willisae and A. millepora (Negri et al 2001). The species Pseudoalteromonas luteoviolacea also induces metamorphosis in the larvae of the polychaete Hydroides elegans (Huang & Hadfield 2003) and the sea urchin Heliocidaris erythrogramma (Huggett et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, this and other studies have demonstrated some connection between metamorphosis of marine invertebrate larvae and bacterial species of the genus Pseudoalteromonas (Hadfield 2011). Species belonging to this genus have been shown to induce settlement of the larvae of the hydrozoan Hydractinia echinata (Müller 1973, Seipp et al 2007) and the corals Acropora willisae and A. millepora (Negri et al 2001). The species Pseudoalteromonas luteoviolacea also induces metamorphosis in the larvae of the polychaete Hydroides elegans (Huang & Hadfield 2003) and the sea urchin Heliocidaris erythrogramma (Huggett et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Calcareous substrata, such as coral skeleton or rubble without CCA may also induce settlement (Heyward & Negri 1999). In addition to the CCA-generated morphogens, bacteria associated with CCA have been found to produce cues for the settlement of some coral species, specifically 2 species of Acropora, for which bacteria were inductive both in biofilms and in suspension (Negri et al 2001). Golbuu & Richmond (2007) who studied settlement stimuli for corals in Guam found one coral species (Goniastrea retiformis) that preferred CCA and another (Stylaraea punctata) that preferred biofilm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microorganisms on the substrates trigger a sequence of metamorphosis and settlement, and calcareous algae (Morse et al 1996) and a bacterium (Negri et al 2001) have been identified as environmental inducers for meta morphosis of acroporids' larvae. Following reception of external cues, internal signal cascades are supposed to perform metamorphic reactions, including cell differenti ation, in larvae.…”
Section: Introductionmentioning
confidence: 99%